Aloe Vera and Pear Extract Serum: A Herbal Approach to Intertrigo Management - Patel, Lima; Bhavsar, Puja; Bera, Kinjal; Khristi, Avani; Patel, Khyati; Rede, Pankhita; Patel, Kripa; Patel, Dhwani; Jangir, Vinay (Journal of Neonatal Surgery, 2025)
Background: Intertrigo is an inflammatory skin condition that occurs in newborns, infants and adults, typically affecting skin folds (flexural areas) such as the neck, armpits, groin, and under the chin. It results from a combination of moisture, friction, and microbial overgrowth, leading to redness, irritation, and maceration of the skin. Conventional treatments primarily focus on symptom management, highlighting the need for safer, plant-based alternatives. This study aimed to develop and validate a novel herbal serum containing Aloe vera (Aloe barbadensis) and pear (Pyrus communis) extracts for intertrigo treatment, with an emphasis on formulation optimization and analytical method validation. Methods: The formulation was developed using Carbopol as a gelling agent to ensure optimal viscosity and stability. High-Performance Thin-Layer Chromatography (HPTLC) was employed for qualitative and quantitative analysis of Aloe emodin (Aloe vera) and Oleanolic acid (pear extract). Analytical method validation was performed following ICH Q2(R1) guidelines, evaluating parameters such as linearity, precision, accuracy, robustness, limit of detection (LOD), and limit of quantification (LOQ). Results: The formulated serum exhibited excellent spreadability, pH compatibility, and homogeneity. HPTLC analysis demonstrated well-defined bands for Aloe emodin and Oleanolic acid at optimized Rf values. The method showed linearity (500–1500 ng/spot, R² > 0.999), precision (%RSD < 2%), and accuracy (98–102% recovery). The established LOD and LOQ values confirmed high sensitivity, ensuring reliable quantification of the bioactive markers. Robustness studies demonstrated the stability of the analytical method under minor variations. Conclusion: The developed herbal serum demonstrated promising physicochemical properties and stability, while the validated HPTLC method provided accurate and reproducible quantification of Aloe emodin and Oleanolic acid. These findings support the potential of this novel herbal formulation as a natural therapeutic option for intertrigo.